Boron distributions in individual core–shell Ge/Si and Si/Ge heterostructured nanowires. Issue 47 (22nd November 2016) - Han, Bin; Shimizu, Yasuo; Wipakorn, Jevasuwan; Nishibe, Kotaro; Tu, Yuan; Inoue, Koji; Fukata, Naoki; Nagai, Yasuyoshi
Abstract : The distributions of boron (B), one of the most important impurities, in Ge/Si and Si/Ge core–shell nanowires were studied by atom probe tomography. Abstract : Ge/Si and Si/Ge core–shell nanowires (NWs) have substantial potential for application in many kinds of devices. Because impurity distributions in Ge/Si and Si/Ge core–shell NWs strongly affect their electrical properties, which in turn affect device performance, this issue needs urgent attention. Here we report an atom probe tomographic study of the distribution of boron (B), one of the most important impurities, in two kinds of NWs. B atoms were doped into the Si regions of Ge/Si and Si/Ge core–shell NWs. It was found that the B atoms were randomly distributed in the Si shell of the Ge/Si core–shell NWs. In the Si/Ge core–shell NWs, on the other hand, the B distributions depended on the growth temperature and the B2 H6 flux. With a higher growth temperature and an increased B2 H6 flux, the B atoms piled up in the outer region of the Si core. However, the B atoms were observed to be randomly distributed in the Si core after decreasing both the growth temperature and the B2 H6 flux.